The Implementation Strategy of Religious Culture in Madrasah - Maarif, Muhammad Anas; Wardi, Moh; Amartika, Surya (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
The importance of conducting in-depth research related to madrasah culture that is applied by madrasa is related to how teachers perform with exemplary, seriousness and responsibility. This research is a type of qualitative research with the approach used is a case study. The research location is in Madrasah Aliyah Darul Falah Cermee Bondowoso. Data collection methods obtained from observation, documentation, and interviews. Data analysis was performed by selecting and compiling the data obtained, then processed and analyzed so that conclusions can be drawn. The results of research on the application of religious culture at Madrasah Aliyah Darul Falah Cermee Bondowoso are: Planning, implementation and evaluation. Religious cultural program planning is carried out by making the vision and mission of the madrasa in accordance with the objectives of religious culture and national goals. The implementation stage of religious culture is carried out with extracurricular and extracurricular activities. The intraculular process or what is called the process of applying religious culture through learning. Meanwhile, religious culture in extracurricular activities and habituation such as smiling greetings and greetings, reciting prayers regularly in the morning, cleanliness, exemplary, and giving gifts and punishments. Implementation of evaluation through semester examination activities and evaluation of madrasah administrators in the discipline of teachers and students. The recommendation for further research is to take a cultural or ethnographic approach so that the research results are more comprehensive